Cassette incubation followed by bioanalysis using high-resolution MS for in vitro ADME screening assays. (March 2012) - Zhang, Jun; Maloney, Jennifer; Drexler, Dieter M; Cai, Xianmei; Stewart, Jeremy; Mayer, Chris; Herbst, John; Weller, Harold; Shou, Wilson Z
Background: High-resolution MS (HRMS) has recently received a considerable interest in quantitative bioanalysis using full-scan acquisition mode. The benefits include complete elimination of compound-specific MS method development, and simultaneous collection of mass spectral data on both targeted and non-targeted components. One additional advantage that has not been widely discussed is its suitability for simultaneous quantitation of, theoretically, an unlimited number of compounds, which is not possible with selected reaction monitoring (SRM) on a triple quadrupole mass spectrometer.Materials & Methods: We took advantage of this unique bioanalytical capability of HRMS and developed a novel in vitro ADME workflow of cassette incubation of as many as 32 compounds, followed by quantitative bioanalysis using full-scan acquisition on an Orbitrap HRMS. The workflow was evaluated for a serum protein-binding assay and a parallel artificial membrane permeability (PAMPA) assay.Results: The bioanalytical assay displayed acceptable sensitivity, selectivity and linearity for all compounds in the cassettes, and the biological results obtained using this approach were similar to those from discrete incubation and analysis, demonstrating the feasibility of the workflow. Additional benefits of this platform include a saving of analysis time due to the reduced sample numbers from the cassette approach, as well as cost saving due to the reduction in the required assay reagents.Conclusion: Cassette incubation with bioanalysis using HRMS is a feasible approach for high-throughput in vitro ADME assays evaluated in this study.